Cr(VI) adsorption onto a new composite prepared from Meidum black clay and pomegranate peel extract: Experiments and physicochemical interpretations. Issue 4 (August 2021) - Ramadan, H.S.; Mobarak, Mohamed; Lima, Eder C.; Bonilla-Petriciolet, Adrián; Li, Zichao; Seliem, Moaaz K.
Abstract: A new hybrid composite was synthesized through the interaction between pomegranate peel extract (PPE) and Meidum black clay (MBC). This interaction effect (between PPE and MBC) in the surface chemistry, structure, and textural properties of MBC was evaluated via different techniques such as XRD, FTIR, SEM, zeta potential, and BET surface area. The adsorption behavior of the fabricated MBC/PPE composite against Cr(VI) was investigated at different temperatures (25–50 °C) and pH 2.0. The Freundlich equation fitted well to the Cr(VI) adsorption data at 25, 40, and 50 °C ( R 2 > 0.99 and χ 2 < 1.92). Five statistical physics models were also utilized to calculate and interpret the steric, energetic, and thermodynamic functions related to Cr(VI) adsorption. Physicochemical parameters were obtained with a monolayer model assuming two surface functionalities with different adsorption energies. Sterically, the active sites number ( n ) ranged from 0.85 to 1.86, which indicated that mechanisms of multi–docking and multi–interactions were involved in the removal of Cr(VI) by different MBC/PPE functional groups. From 25° to 50 °C, the active site density ( N M ) decreased from 104.3 to 92.5 mg/g for N 1M, but enhanced from 48.99 to 78.08 mg/g for N 2M . Adsorption capacities at saturations ( Q sat1 and Q sat2 ) were improved with the increment of temperature, thus confirming an endothermic process. Energetically, Cr(VI) uptake by MBC/PPE adsorbent was related to physical interactions (i.e., adsorption energy ranged from 23.32 to 31.1 kJ/mol). Macroscopically, Cr(VI) adsorption onto MBC/PPE was spontaneous based on calculated thermodynamic functions. Overall, the interaction between MBC and PPE presented a novel, eco-friendly, and promising adsorbent for Cr(VI) from contaminated water. Graphical Abstract: ga1 Highlights: Meidum clay and pomegranate peel extract interaction generated a new Cr(VI) adsorbent. Classical and advanced statistical adsorption models were utilized. Cr(VI) adsorption by MBC/PPE was endothermic and governed by physical interactions. Steric, energetic, and thermodynamic parameters were determined and interpreted.